Histological features of advanced colorectal adenomas detected by endoscopy and fecal immunochemical test - Risio, Mauro; Hassan, Cesare; Sottile, Antonino; Saglia, Alberto; Segnan, Nereo; Senore, Carlo (Endoscopy, 2015)
Background and study aims: The detection of advanced adenomas within organized screening programs using either immunochemical fecal occult blood test (FIT) or endoscopy has been associated with the prevention of colorectal cancer. The histological changes and pathogenetic mechanisms that lead to the detection of such lesions by either of these screening methods have not yet been addressed.Patients and methods: The histological specimens of 50 advanced adenomas detected by FIT were compared with those of 50 advanced adenomas detected by primary endoscopy screening that were matched for size and histology. The following variables were systematically recorded: 1) histopathological changes compatible with luminal bleeding induced by ischemia; 2) hypoxia in the adenomatous tissue, assessed through the expression of carbonic anhydrase IX; and 3) microvessel quantitative analysis, evaluated by CD31 and CD105 immunostains. All specimens were reviewed blindly by an expert gastrointestinal pathologist.Results: Histopathological changes associated with ischemia-related luminal bleeding were significantly more frequent in FIT-positive than in endoscopy-detected advanced adenomas (78 % vs. 14 %; P < 0.001). Carbonic anhydrase IX expression was also significantly higher in FIT-detected advanced adenomas (immunohistochemical score: 12.0 vs. 4.1; P < 0.001). Conversely, no differences were found in microvessel density.Conclusions: The detection of advanced adenomas by FIT screening appears to be related to ischemia-associated luminal bleeding, which, in turn, may be due to periods of hypoxia. The absence of such changes in endoscopy-detected advanced adenomas would suggest that the two screening methods may be complementary for the detection of advanced neoplasia within organized screening programs.